The consequences of long-term therapy with proton pump inhibitors - Drygała, Zuzanna; Wyrwał, Julia; Krasuska, Martyna; Nowak, Karolina; Olejarz, Zuzanna; Zielińska, Zuzanna; Słowik, Magdalena; Nowak, Karolina; Nieć, Maria; Gierlach, Katarzyna (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Proton pump inhibitors (PPIs) were first developed in the late 1970s and introduced to the market in 1989. They are one of the most commonly prescribed medications worldwide. PPIs reduce gastric acid secretion in the stomach by inhibiting the hydrogen-potassium ATPase enzyme. They have revolutionized the treatment of diseases related to excessive stomach acid secretion. Among the drugs belonging to this class, we should mention omeprazole, esomeprazole, pantoprazole, lansoprazole, dexlansoprasole and rabeprazole. A brief description of the state of knowledge: Since the 1990s, the use of proton pump inhibitors has been consistently increasing. Doctors prescribe these drugs more frequently, in higher doses, and for longer durations, although such practices are only sometimes fully justified. Although using them for a short period (less than eight weeks) is relatively safe, there is growing evidence of possible risks linked to their extended use. Many studies highlight the impact of long-term therapy on the development of tumors, deficiencies in micronutrients, the functioning of the skeletal, urinary, nervous, and cardiovascular systems, and the development of infections and diabetes. Summary (conclusions): Indeed, long-term therapy with proton pump inhibitors has an impact on the functioning of the body. Considering the increasing popularity of proton pump inhibitors and their expanding use, it is worth contemplating a more prudent prescription of these drugs by doctors. It should also be noted that the majority of studies are based on prescription PPIs. Future researchers must also take over-the-counter (OTC) medications into account.